Legal Age Equality in Marriage According to Indonesian Positive Law in the Studies of Gender and Maqāṣid Al-Sharia - Ismail, Ismail; Busyro, Busyro; Yenti, Endri; Amin, Saiful; Alwana, Hanif Aidhil (De Jure: Jurnal Hukum dan Syari'ah, 2023)
Law No. 16 of 2019 has set the legal age allowed for marriage to 19 for both men and women and this change, from previously 19 for men and 16 for women, has sparked a discussion among scholars. This study aims to examine this provision from the aspects of gender and maqāṣid al-sharia. This research uses a normative juridical approach with qualitative data analysis, which concludes that equalizing the age of marriage between men and women at 19 years old has realized gender equality in terms of eliminating discrimination against women in obtaining their rights such as health, education, and economic rights, and can eliminate the dominance of a husband over his wife because marrying at the same age (adulthood) will have a positive effect on the way the couple treats each other. Marriage age equality from the perspective of maqāṣid al-sharia has realized maqāṣid al-tab'iyah (supporting objectives) at the level of al-taḥsīniyah because it makes marriage more prestigious and dignified.